Penerapan Konsep Lean Manufacturing Untuk Redesign Tata Letak Fasilitas Dengan Pendekatan Value Stream Mapping Pada UMKM Roti Agifa - Ridwan Adi Setiabudi; Nabila Kurnia Ramadhani; Eko Apriyana; Fadila Woro Wulandari; Dista Amelia (Pusat Riset dan Inovasi Nasional, 2025)
Agifa Roti is one of the small and medium enterprises (SMEs) engaged in the food industry, located in Warungboto, Umbulharjo District, Yogyakarta City, Special Region of Yogyakarta. The products produced are in the form of basic ingredients for sweet bread, in the production process it is still traditional without using the help of machines only during the baking process using a gas-fueled oven and mixer to make dough. facing waste constraints in the sweet bread production process, especially in waiting activities (31.07%) and transportation (8.90%). This waste is caused by the less than optimal layout of facilities, with a distance of movement between work stations reaching 810.99 cm. This study aims to identify waste, reduce waste, and increase production efficiency through the application of the Lean Manufacturing method with the Value Stream Mapping (VSM) approach including the calculation of Material Handling Costs (OMH) to assess cost efficiency. Research methods related to cycle time, lead time, changeover time, and facility layout. Based on the research results, it shows that the application of the Lean Manufacturing method with the VSM approach is able to reduce the distance of movement between work stations by 29.2%, production cycle time by 61.2%, and material handling costs significantly, thereby increasing efficiency, reducing waste, and providing real benefits for the productivity and competitiveness of Roti Agifa MSMEs and similar MSMEs.